Relationship Between Prostate Volume and Lower Urinary Tract Symptom in Health Checkup Subjects - Hyeon Ju Kim; Ji Hyun Moon; 오윤환; 공미희; Kyung Kgi Park; 허정식 (Journal of Urologic Oncology, 18(1), 2020)
Purpose: This study aimed to evaluate the relationship between prostate volume and lower urinary symptom (LUTS) in subjects undergoing health checkup and to know the usefulness of TRUS in health screening. Materials and Methods: The study was conducted in 883 men aged ≥20 years who underwent TRUS for health screening. All participants had filled in the international prostate symptom score (IPSS) and were tested for prostate-specific antigen; prostate volume, central gland volume, and transitional zone index were measured using TRUS. We analyzed the differences in the IPSS by prostate volume and differences in prostate volume by severity of LUTS and correlation between prostate volume and each component of IPSS. Results: There were differences in the total IPSS, storage score, and voiding score between the subjects with prostate volumes of ≥30 mL or not (p=0.027, p=0.037, and p=0.029, respectively). However, the differences were found only for urgency and weak stream. The volume of the severe symptom group was bigger than those of the mild and moderate symptom groups (p=0.002 and p=0.014). The correlation between prostate volume and IPSS was significant only for the between the central volume and nocturia (r=0.112, p＜0.01). Conclusions: The relationship between prostate volume and urinary symptoms showed significant but low correlation and found only in some components. For the accurate diagnosis, it would be more useful to accompany various voiding-related surveys in addition to TRUS during health screening. KCI Citation Count: 1